Lower Income African American Women and HIV/AIDS: The Effect of Contexts on Identity Incorporation - Lisa Baumgartner (Adult Education Research Conference, 2012)
The purpose of this study was to explore how contexts affect the incorporation of the HIV/AIDS identity into the self for lower income African American women. Eleven in-depth interviews were conducted. Situational factors predisposed women to contracting HIV/AIDS and delayed the turning point from their initial emotional reaction. Support from family and friends helped the integration process whereas stigma delayed integration. Race and class negatively affected some women‘s experience of living with HIV/AIDS. These findings have implications for health educators.